Rethinking market regulation helping labor by overcoming economic myths - Drobak, John N. (Oxford University Press, 2021)
This book tackles the plight of workers who lose their jobs from mergers and outsourcing by examining two economic "principles' or narratives that have shaped the perception of the economic system in the U.S. today: (1) the notion that the U.S. economy is competitive, making government market regulation unnecessary, and (2) the claim that corporations exist for the benefit of their shareholders, but not for other stakeholders. Contrary to popular belief, this book demonstrates that many markets are not competitive, but rather are oligopolistic. This conclusion undercuts the common refrain that government market regulation is unnecessary because competition already provides sufficient constraints on business. Part of the lack of competition has resulted from the large mergers over the past few years, many of which have resulted in massive lay-offs. The second narrative has justified the outsourcing of millions of jobs of U.S. workers this century, made possible by globalization. The book argues that this narrative is not an economic principle but rather a normative position. In effect, both narratives are myths, although they are accepted as truisms by many people. The book ties together a concern for the problems of using economic principles as a justification for the lack of government intervention with the harm that has been caused to workers. The book's recommendations for a new regulatory regime is a prescription for helping labor by limiting job losses from mergers and outsourcing"--